THE SHELF LIFE OF HERBAL TEA FROM BELIMBING WULUH (AVERRHOA BILIMBI L.) IS A FUNCTIONAL FOOD FOR TREATING HYPERTENSION : UMUR SIMPAN TEH HERBAL DAUN BELIMBING WULUH (Averrhoa Bilimbi L.) PANGAN FUNGSIONAL PENANGGULANGAN HIPERTENSI - Magfirah Magfirah Ramadani; Abdul Salam; Nurzakiah; Nurhaedar Jafar; Safrullah Amir (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2023)
Introduction: Hypertension is also called a "silent killer" because people with hypertension often do not show symptoms. Hypertension is one of the most common cardiovascular diseases and the most widely borne by the public.  Starfruit leaves have content to lower blood pressure that is methanol extract containing flavanoids as antioxidants. Aim: This study aims to determine how long the shelf life of starfruit leaf tea products (Averrhoa  Bilimbi L.) to patients with hypertension by using the Accelerated Shelf Life Test (ASLT)        Arrhenius model. Materials and Methods:  This study is a descriptive study with laboratory analysis. Starfruit leaf tea stored for 14 days at a temperature of 25oC, 35oC and 45oC by measuring the parameters of water content. The Data is then calculated based on the Arrhenius equation. Processing and analysis of data using Microsoft excel and presented in the form of tables and narratives. Results: Water content in starfruit leaf tea products decreased during storage 0 to 14 days. Reaction kinetics of degradation follows zero-order reactions. Tea stored at 25oC has a longer shelf life of 112 days than storage at 35oC and 45oC. The temperature of 35oC has a shelf  life of 60 days. The products are stored  at  a temperature of 45oC has a shelf life of 39 Day. Conclusion: The higher the storage temperature, the shorter the shelf life of the bilimbi leaf tea product.